Pengaruh Model Pembelajaran Snowball Throwing Berbantuan Media Video Interaktif Terhadap Kemampuan Komunikasi Matematis Siswa Kelas IV SDN Windusari - Solaekah, Sri Maratus; Purwanti, Kartika Yuni (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The purpose of this study was to determine the effect of the interactive video-assisted Snowball Throwing learning model on the mathematical communication skills of grade IV students at SDN Windusari. This study uses a quantitative approach with the type of experimental method, namely Quasi-Experimental design in the form of Non-Equivalent Control Group Design. The population in this study were all fourth-grade students at SDN Windusari. As for the sample in this study were fourth grade students at SDN Windusari 1 and fourth grade students at SDN Windusari 2. Data collection techniques used observation, questionnaires, tests, unstructured interviews, and documentation. The data analysis technique used is the Independent Sample T-Test and Simple Linear Regression Test. The results of this study indicate that: (1) There is an average difference in students' mathematical communication skills between the control class and the experimental class, which can be seen from the Independent Sample T-Test and the tcount > ttable (5.542 > 2.013) with a sig .(2-tailed) i.e., 0.000 <0.05 then Ho is rejected and Ha is accepted. (2) There is an influence of the Snowball Throwing learning model assisted by interactive video media on students' communication skills, which can be seen from the Simple Linear Regression Test and a significance level of 0.000 <0.05 is obtained with an R square value of 0.691 = 69.1%, then This regression model can affect the participation variable. So it can be concluded that the Snowball Throwing learning model assisted by interactive video media has an effect on the mathematical communication abilities of grade IV students at SDN Windusari 1.